FAULT-TOLERANCE RESEARCH OF NAVIGATIONAL NONORTHOGONAL MEASURING INSTRUMENTS - Sushchenko, Olga; Osipenko, Irina (Proceedings of National Aviation University (archive), 2006)
Problems of fault-tolerance and possibilities of reliability growth of the nonorthogonal redundant navigational measuring instruments are studied.